2017
DOI: 10.1515/acm-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Levels and Autonomic Control of Heart Rate in Healthy Subjects

Abstract: A b s t r a c tIntroduction: There is an increase in level of stress in the general population because of the social, personal and professional demands. Currently, there are only simple tools that can safely measure this stress such as levels of cortisol and heart rate variability (HRV).Objective: To analyze the relationship between salivary cortisol and the cardiac autonomic modulation. Methods: A total of fifty-one male and female subjects between 18 and 40 years old were evaluated. Saliva collection was ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The cortisol levels are low at 8:00 and high at 12:00 35. Although a previous study suggested a significant influence of cortisol on HRV 36, another investigation was unsuccessful in finding a significant association between cortisol and HRV 37.…”
Section: Discussionmentioning
confidence: 92%
“…The cortisol levels are low at 8:00 and high at 12:00 35. Although a previous study suggested a significant influence of cortisol on HRV 36, another investigation was unsuccessful in finding a significant association between cortisol and HRV 37.…”
Section: Discussionmentioning
confidence: 92%